P020 COLONIC INHIBITION OF PHOSPHATASE AND TENSIN HOMOLOG (PTEN) INCREASES COLITOGENIC BACTERIA, INDUCING COLITIS IN IL10 DEFICIENT MICE. (18th January 2018) - Rhee, Sang Hoon; Im, Eunok; Pothoulakis, Charalabos
Abstract: Background: Pten (phosphatase and tensin homolog) regulates microbe-induced immune responses in the gut. Thus, the intestinal deletion of Pten accelerates colitis development in Il10-/- mice. Since some of ambient pollutants inhibit Pten function, and exposure to ambient pollutants may increase IBD incidence, it is of importance to study how Pten inhibition could affect colitis development in genetically susceptible hosts. Methods: With human colonic mucosa biopsies from pediatric Ulcerative colitis and non-IBD control subjects, we quantified the mRNA levels of PTEN gene and the gene involved in IL10 signaling. The data from the human tissues were corroborated by treating Il10-/-, Il10rb-/- and wild type C57BL/6 mice with Pten specific inhibitor VO-OHpic. The severity of mouse colitis was evaluated by measuring the tissue histology and cytokine production. Gut microbiome was analyzed by sequencing the 16S ribosomal RNA gene with mouse fecal samples. Results: PTEN and IL10RB mRNA levels were reduced in the human colonic mucosa of pediatric Ulcerative colitis relative to non-IBD subjects. Intracolonic administration of the Pten inhibitor caused colitis in Il10-/- mice, characterized by reduced body weight, marked colonic damage, and increased production of inflammatory cytokines, while Il10rb-/- and wild type C57BL/6 mice treated with the inhibitor did not develop colitis. Pten inhibitor treatment changed the fecal microbiome with increased proportions of colitogenic bacteria Bacteroides and Akkermansia in Il10-/- mice. Conclusions: Loss of Pten function increases the levels of colitogenic bacteria in the gut, thereby inducing deleterious colitis in an Il10 deficient condition.